Penetrating cardiac injuries: A 36-year perspective at an urban, Level I trauma center. Issue 4 (October 2016) - Morse, Bryan C.; Mina, Michael J.; Carr, Jacquelyn S.; Jhunjhunwala, Rashi; Dente, Christopher J.; Zink, John U.; Nicholas, Jeffrey M.; Wyrzykowski, Amy D.; Salomone, Jeffrey P.; Vercruysse, Gary A.; Rozycki, Grace S.; Feliciano, David V.
Abstract : BACKGROUND: This study evaluates patterns of injuries and outcomes from penetrating cardiac injuries (PCIs) at Grady Memorial Hospital, an urban, Level I trauma center in Atlanta, Georgia, over 36 years. METHODS: Patients sustaining PCIs were identified from the Trauma Registry of the American College of Surgeons and the Emory Department of Surgery database; data of patients who died prior to any therapy were excluded. Demographics and outcomes were compared over three time intervals: Period 1 (1975–1985; n = 113), Period 2 (1986–1996; n = 79), and Period 3 (2000–2010; n = 79). RESULTS: Two hundred seventy-one patients (86% were male; mean age, 33 years; initial base deficit = −11.3 mEq/L) sustained cardiac stab (SW, 60%) or gunshot wounds (GSW, 40%). Emergency department thoracotomy was performed in 67 (25%) of 271 patients. Overall mortality increased in the modern era (Period 1, 27%, vs. Period 2, 22%, vs. Period 3, 42%; p = 0.03) along with GSW mechanisms (Period 1, 32%, vs. Period 2, 33%, vs. Period 3, 57%; p = 0.001), GSW mortality (Period 1, 36%, vs. Period 2, 42%, vs. Period 3, 56%; p = 0.04), and multichamber injuries (Period 1, 12%, vs. Period 2, 10%, vs. Period 3, 34%; p < 0.001). In Period 3, GSWs (n = 45) resulted in multichamber injuries in 28 patients (62%) and multicavity injuries in 19 patients (42%). Surgeon-performed ultrasound accurately identified pericardial blood in 55 of 55 patients in Period 3. CONCLUSIONS: Increased frequency of GSWs in the past decade is associated with increased overall mortality, multichamber injuries, and multicavity injuries. Ultrasound is sensitive for detection of PCI. LEVEL OF EVIDENCE: Therapeutic study, level IV; epidemioligc study, level III.